Efisiensi Proyek Perumahan Green Teksin Tegal melalui Rekayasa Nilai: Pendekatan AHP dan Analisis Biaya Siklus Hidup - Putra, Benny Hermana; Wulandari , Dewi Ayu (Jurnal Manajemen Teknologi & Teknik Sipil, 2025)
The construction sector significantly contributes to Indonesia's economic growth. However, this sector continues to face challenges in achieving cost efficiency and sustainability, particularly in medium-scale housing projects. This study aims to evaluate the application of Value Engineering (VE) in the Green Teksin Tegal Phase 2 Housing Project, focusing on optimizing material selection, construction techniques, and project management to enhance efficiency and effectiveness. A combined quantitative and qualitative methodology was utilized, incorporating the Analytical Hierarchy Process and Life Cycle Cost Analysis. Data collection involved project documentation reviews, structured stakeholder interviews, and site observations. Findings identified substantial cost-saving alternatives, including thin plastering (skimming), low cement-sand mixture concrete blocks, and laminated High-Density Fiberboard doors. These alternatives demonstrated savings of approximately 8.46%, 16.81%, and 20%, respectively. The study acknowledges obstacles such as fluctuating material prices, environmental regulations, and stakeholder preferences, recommending strategic solutions to mitigate these issues. The project's long-term economic viability and environmental sustainability can significantly improve by addressing these challenges. This research contributes valuable insights into cost-effective project execution, highlighting Value Engineering’s potential to enhance future residential construction projects' quality, sustainability, and economic viability, ultimately benefiting broader urban development and environmental conservation initiatives.